2020
DOI: 10.1590/scielopreprints.1081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Consumo De Mídias Sexualmente Explícitas E Sexo Anal Desprotegido Em Homens Que Fazem Sexo Com Homens

Abstract: O objetivo deste estudo foi avaliar a influência do consumo de mídia sexualmente explicita (MSE) do tipo “bareback” na prática de sexo anal sem preservativo por homens que fazem sexo com homens (HSH). Para tanto, foi criada uma página no Facebook®, com um link que direcionava os participantes para o questionário do estudo. Foram incluídos os usuários que se identificavam como homem cisgênero, com 18 anos ou mais de idade e que praticaram sexo com outro homem nos 12 meses anteriores a pesquisa. Os dados foram c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
0
0
2
Order By: Relevance
“…Concerning male homosexual relations, a study confirmed the hypothesis that the use of pornography among men is associated with viewing pornography during sex with the partner, causing the partner to reproduce scenes and practices from the pornographic film during sex, as way of obtaining sexual pleasure (18) . In this group, the preference for SEM without condoms is classic and similar to what has already been described by other authors, corroborating the existence of a direct link between the preference for "bareback" scenes and the intention of having sex without condoms (19)(20) .…”
Section: Discussionsupporting
confidence: 90%
“…Concerning male homosexual relations, a study confirmed the hypothesis that the use of pornography among men is associated with viewing pornography during sex with the partner, causing the partner to reproduce scenes and practices from the pornographic film during sex, as way of obtaining sexual pleasure (18) . In this group, the preference for SEM without condoms is classic and similar to what has already been described by other authors, corroborating the existence of a direct link between the preference for "bareback" scenes and the intention of having sex without condoms (19)(20) .…”
Section: Discussionsupporting
confidence: 90%
“…Os resultados apresentaram maior frequência de nível de evidência IV, inferindo a que há a necessidade de outros tipos de estudos voltados a temática, para fins de maior evidência científica. Verificou-se maior produção de estudos voltados a temática desta revisão nos Estados Unidos da América, e tal fato pode estar relacionado ao país ser um dos maiores produtores de Mídias Sexualmente Explícitas [4].…”
Section: Discussionunclassified
“…As mídias correspondem a um meio de compartilhamento de informações e tornaram-se parte integrante do estilo de vida dos jovens, o que levou a mudanças dramáticas na maneira como eles percebem e praticam suas relações sociais, criando espaços onde os indivíduos podem moldar e expressar sua sexualidade [2,3]. Logo, o compartilhamento de Mídias Sexualmente Explícitas corresponde a materiais que envolvam a prática e/ou órgãos sexuais [4].…”
Section: Introductionunclassified